The possibility of using the WMS system to improve storage management: the case of a construction company in the area of Mata Mineira - Rocha, Jessica Taveira da; Oliveira, Luiz Alberto Teixeira; Oliveira, Mário César Fialho de; Abreu, Sanderson Rocha de; Oliveira, Patricia Werneck Silva de (Brazilian Journal of Production Engineering, 2021)
The need to expand activities and gain competitive advantage is a reality in the current market scenario. In this context, the organization’s internal processes affect its performance in the market. Thus, the concern with storage management is of great relevance, as it has the power to guarantee that new demands are met. This article is an applied, qualitative, descriptive research, with the development of a case study, with the purpose of studying and identifying the problems that affect the storage and stock management system of the Distribution Center of the chain of stores. a building materials dealership. The objective is to analyze the warehouse management in order to diagnose existing problems, and indicate possible gains with the adoption of a Warehouse Management System (WMS) system. Through interviews with employees, sector supervisors, site visits and reports with analytical data. As a result, the identification of several problems involving the organization’s Storage Management, concluding that it does not have a computerized system for such service and that its stock does not have product addressability, which causes difficulties in order picking, carrying out inventory, and ends up compromising its stock accuracy. As a way of proposing improvement for the current situation of storage and better stock planning, the classification of the ABC curve was carried out, and the advantages were demonstrated, the acquisition and implementation of a WMS system was suggested, which proved capable of mitigating the main problem that currently affects the organization.